Detección fenotípica y molecular de resistencia a meticilina en S. aureus - Castellano-González Maribel J; Perozo-Mena Armindo J; Vivas-Vega Rosana (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2008)
Abstract: Detecting methicillin resistance is complicated due to the heterogeneity of its phenotypic expression, making its detection difficult in the laboratory; this has led to the development of several techniques to increase its expression in vitro. Four techniques for detecting methicillin resistance were evaluated: the disk diffusion method with oxacillin (OX, 1 µg) and cephoxitin (FOX, 30 µg); the screening test, minimum inhibitory concentration (MIC) and detection of PBP2a, using the presence of mecA gen as a reference method; 286 strains of S. aureus, were processed. The sensibility (SEN), specificity (SPE), positive predictive value (PPV), negative predictive value (NPV) and efficiency (EFC) of each method were determined. A total of 50 oxacillin resistant, PBP2a positive (mecA positive) strains were obtained. Sensibility of the OX disk was 99.14%; and of the FOX disk was 100%. The SEN, PPV, NVP and EFC of the other methods were 100%. All the tests, except the OX disk diffusion method (99.14% of ESP), were 100% specific. Resumen: La detección de resistencia a meticilina es complicada debido a la heterogeneidad de su expresión fenotípica; dificultando su detección en el laboratorio, lo que ha conducido al desarrollo de varias técnicas para incrementar su expresión in vitro. A fin de evaluar cuatro técnicas para la detección de resistencia a meticilina: método de difusión del disco con oxacilina (OX, 1 µg) y cefoxitin (FOX, 30 µg); screening test, concentración inhibitoria mínima (CIM) y detección de PBP2a, utilizando la presencia del gen mecA como método de referencia, se procesaron 286 cepas de S. aureus. Se determinó la sensibilidad (SEN), especificidad (ESP), valor predictivo positivo (VPP), valor predictivo negativo (VPN) y eficiencia (EFC) de cada uno de los métodos. Se obtuvo un total de 50 cepas resistentes a oxacilina, PBP2a positivos (mecA positivos). La sensibilidad del disco de OX fue de 99.14% y la de FOX fue de 100%. La SEN, VPP, VPN y EFC de los otros métodos fue de 100%. Todas, a excepción del método de difusión del disco de OX (ESP de 99.14), resultaron 100% específicos.